Convergence Rate for Difference Schemes for Polyhedral Nonlinear Parabolic Equations (Journal of Computational Mathematics, 2018)
We build finite difference schemes for a class of fully nonlinear parabolic equations. The schemes are polyhedral and grid aligned. While this is a restrictive class of schemes, a wide class of equations are well approximated by equations from this class. For regular $(C^{2,α})$ solutions of uniformly parabolic equations, we also establish of convergence rate of $\mathcal{O}(α)$. A case study along with supporting numerical results is included.